Effect of Moisture Content of Green Sand on The Casting Defects - Nanang Qosim; AM Mufarrih; Ali Sai’in; A. Hanif Firdaus; Fina Andika F. A.; Ratna Monasari; Zakki F. Emzain (Journal of Applied Engineering and Technological Science (JAETS), 2020)
In this study, three percentages of moisture content on the green sand were benchmarked to be observed their effects on the casting defects. The metal used is scrap Al-Si with wt% of Al 59.7. The metal was melted in a furnace at 550 ºC then poured into sand molds and cooled for 24 hours before it can be removed, cleaned, and finished. There were prepared three specimens for each benchmark. Qualitative observation of defects was done by physical observations on the surface of the specimens. The observations show that on the moisture content of 2.5%, there is a defect in the form of porosity. Defects in the form of drops, misruns, blowholes, and shrinkage cavity are found on the benchmark 3.5%. The most severe defects are found on the benchmark 4.5% in the form of buckles and severe shrinkage cavities that are found in almost all specimens.